2017
DOI: 10.1111/1440-1681.12891
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pyridine derivative inducing senescence in ovarian cancer cell lines via P21 activation

Abstract: Cellular senescence is a state of irreversible cell growth arrest. Increasing evidence suggests that cellular senescence contribute to tumour suppression in vivo. However, only a few anti-cancer drugs have been discovered to induce cellular senescence. Searching for new compounds which can inhibit cancer cell growth by inducing senescence is becoming one of the most attractive research fields. To test the effects of candidate compounds on cancer cell growth, cell proliferation assays, senescence-associated β-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
(122 reference statements)
2
9
0
Order By: Relevance
“…7) Recent studies have shown that cellular senescence contributes to the anticancer effects of chemotherapeutic drugs, and cellular senescence-inducing agents might be a feasible strategy. 8,9,30) In the current study, we found that low concentration of ART promotes cellular senescence in NSCLC cells. As cellular senescence can be controlled by CDK inhibitor p16 INK4a (p16), and affects the outcome of cancer therapy.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…7) Recent studies have shown that cellular senescence contributes to the anticancer effects of chemotherapeutic drugs, and cellular senescence-inducing agents might be a feasible strategy. 8,9,30) In the current study, we found that low concentration of ART promotes cellular senescence in NSCLC cells. As cellular senescence can be controlled by CDK inhibitor p16 INK4a (p16), and affects the outcome of cancer therapy.…”
Section: Discussionsupporting
confidence: 56%
“…6) Cellular senescence has been considered as an important factor in aging and age-related disease, and it is a seductive target for therapeutic exploitation. 7) Increasing studies have revealed that cellular senescence leads to tumor suppres-sion, 8,9) and only a few anti-tumor agents have been developed to promote cellular senescence. Therefore, developing new agents to disturb cancer cell proliferation by promoting cellular senescence is becoming a research focus.…”
Section: Introductionmentioning
confidence: 99%
“…Senescent cells typically display an enlarged morphology and an enhanced SA-β-gal activity. The specific molecular characteristics of senescent cells include the upregulation of p16 and α-SMA [28,29]. All these features were observed in the CAFs isolated in this study, indicating that the CAFs were more senescent than the NFs.…”
Section: Discussionsupporting
confidence: 50%
“…The endogenous control was β-actin. Immunoblotting was performed using the antibodies listed in Supplementary Table 1 , and as described in previous studies ( 45 , 46 ). β-actin was used as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…SA-β-Gal staining was performed as previously described (45)(46)(47). Briefly, treated cells were fixed in 2% formaldehyde/0.2% glutaraldehyde in PBS for 5 min at room temperature.…”
Section: Sa-β-gal Stainingmentioning
confidence: 99%